Daily diary study of loneliness, alcohol, and drug use during the COVID‐19 Pandemic. (26th August 2022) - Bragard, Elise; Giorgi, Salvatore; Juneau, Paul; Curtis, Brenda L.
Abstract: Background: Research conducted during the COVID‐19 Pandemic has identified two co‐occurring public health concerns: loneliness and substance use. Findings from research conducted prior to the pandemic are inconclusive as to the links between loneliness and substance use. This study aimed to measure associations of loneliness with three different types of substance use during COVID‐19: daily number of alcoholic drinks, cannabis use, and non‐cannabis drug use. Method: Data were obtained between October 2020 and May 2021 from 2, 648 US adults (Mage  = 38.76, 65.4% women) diverse with respect to race and ethnicity using online recruitment. Participants completed baseline surveys and daily assessments for 30 days. A daily loneliness measure was recoded into separate within‐ and between‐person predictor variables. Daily outcome measures included the number of alcoholic drinks consumed and dichotomous cannabis and non‐cannabis drug use variables. Generalized linear multilevel models (GLMLM) were used to examine within‐ and between‐person associations between loneliness and substance use. Results: The unconditional means model indicated that 59.0% of the variance in the daily number of alcoholic drinks was due to within‐person variability. GLMLM analyses revealed that, overall, people drank more on days when they felt a particularly high or particularly low degree of loneliness (positive quadratic effect). There was a negative and significant within‐person association between daily loneliness and the likelihood of cannabis use. There was also a positive and significant within‐person association between daily loneliness and the likelihood of non‐cannabis drug use. Conclusions: Associations between loneliness and substance use vary with substance type and whether within‐ or between‐person differences are assessed. These findings are relevant to the persistence of substance use disorders and thus of potential clinical importance. Individuals who do not experience severe loneliness at intake but who show daily increases in loneliness above baseline levels are at heightened risk of alcohol and non‐cannabis drug use. Future research could profitably examine just‐in‐time adaptive interventions that assess fluctuations in loneliness to prevent the development or exacerbation of substance use disorders. Abstract : This daily diary study aimed to identify associations of loneliness and three different types of substance use during COVID‐19: daily number of alcoholic drinks, cannabis use, and noncannabis drug use. A large sample of US adults ( N  = 2648) was recruited online to complete daily surveys. Multi‐level modeling revealed that overall, people drank more on days participants felt a particularly high or particularly low degree of loneliness. Loneliness was a risk factor for noncannabis drug use but not cannabis use.